Basal ganglia hyperdensity on computerised tomography of brain : a rare finding of non-ketotic hyperglycemia - Ng, VH; Wan Nor Aida WMS; Ahmad Khaldun Ismail (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Hyperdensity of basal ganglia in computed tomography (CT) of brain is alwaysrecognised as hemorrhagic stroke or calcification. Features of hyperglycemia include muscle weakness, hypotonia, pyramidal tract signs and hemichorea-hemiballismus (HC-HB), which mimic the symptoms of stroke. Hyperdensity of the basal ganglia was reported in patient with non-ketotic hyperglycemia (NKH). Inability to recognize the hyperdensity in CT brain as a feature of NKH may lead to failure of treatment. Early recognition and reversal of hyperglycemia will improve the outcome. This was a case of an atypical presentation of stroke-like symptoms with the neuroimaging finding showing asymmetric hyperdensity of basal ganglia. Neurological examination failed to elicit any sign of HC-HB. Laboratory test showed hyperglycemia with absence of acidosis and ketonaemia. The patient was diagnosed having basal ganglia hemorrhage and referred to the Neurosurgical team. However, the stroke-like symptoms completely resolved following the normalization of glucose level. This is the only other reported case of NKH with typical neuroimaging features not associated with HC-HB. One should be aware of the possibility of NKH in the absence of movement disorder with asymmetric basal ganglia hyperdensity in CT brain. Misinterpretation as acute intracranial bleeding may result in suboptimal management of the true underlying cause.